Comparison between digital panoramic radiography and cone-beam computed tomography in measuring presurgical dental implant vertical height at posterior mandible / Ayob M.A.M ... [et al.] - Ayob, M.A.M; Md Jasin, J.S.; Suparman, M.K.; Reduwan, N.H. (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
bjectives: This study aims to evaluate the reliability of panoramic radiograph in comparison to cone beam computed tomography for posterior mandibular pre-implant assessment. Materials and Methods: A retrospective evaluation of the panoramic (PAN) and CBCT images in complete, partially edentulous, and dentate patients was conducted on 66 cases for presurgical dental implant assessment. Assessment of the vertical bone height was conducted by dividing the posterior mandible region into anterior (first premolars to second premolars) and posterior (first molars to second molars) segments. The average mesiodistal crown dimensions from each segment were measured as a midpoint. The reference point to measure the vertical bone height was established from the alveolar crest to the superior border of mandibular canal. Therefore, the measurement will begin at the midpoint of total mesiodistal crown dimension of each segment from the alveolar crest to the superior border of mandibular canal. All measurements were independently performed by two observers thrice on each modality. Results: A paired comparison between PAN and CBCT images in measuring the presurgical dental implant vertical height from alveolar crest to the superior border of mandibular canal (paired t-tests) showed statistically significant difference in the mean difference of vertical bone height at each region between PAN and CBCT (p<0.001). Conclusion: PAN radiograph provides sufficient information for presurgical implant assessment at the posterior mandible in routine cases or during the unavailability of CBCT at the clinic. However, CBCT remains the best imaging modality for presurgical implant assessment as it has a minimal magnification error.